Eosinophilic Esophagitis Is an Underlying Cause for Gastrointestinal Concerns in Children - Lee, Kunsong; Furuta, Glenn T.; Nguyen, Nathalie (Frontiers in Pediatrics, 2018)
Eosinophilic esophagitis (EoE) is a chronic immune antigen-mediated disorder characterized by symptoms of esophageal dysfunction in combination with dense esophageal eosinophilia. The clinical presentation of EoE can vary depending on children’s age and their ability to report symptoms, therefore a high index of suspicion for EoE is required because children and teenagers may develop coping strategies around eating. The development of symptoms measurement tools in EoE assists in not only assessing symptoms, but also coping strategies children may have developed. While the diagnosis of EoE requires endoscopic evaluation with histologic assessment of esophageal mucosal biopsy samples, several emerging methods to assess and survey the esophageal mucosa have been developed. Advances in the field to better understand the natural history, clinical and molecular features of phenotypes in EoE will be important in considering novel therapeutic options and assessing outcomes.